Physical Intimate Partner Violence Concordance Rates in Couples: Does CTS2 Item Order Matter? - Pollard, Deanna L. (Journal of interpersonal violence, 2023)
Intimate partner violence (IPV) concordance rates between partners are low across national, community, and clinical samples. Discordance between partners’ IPV reports is problematic given that self-report questionnaires, such as the CTS2, are commonly used to assess IPV. Moreover, most research is based solely on the report of one partner. Some have attributed this discordance to how CTS2 items are presented. The CTS2 presents items inquiring on the frequencies of perpetration by oneself and then one’s partner in pairs. The present study examined whether IPV concordance rates improve if couples are administered a version of the CTS2 where all items assessing their partner’s behaviors are presented first, followed by items assessing the respondents’ behaviors. Additionally, the present study examined whether correlations between self-reported and partner-reported perpetration and victimization differ depending on the order in which CTS2 items are presented. Two samples of heterosexual couples were recruited from a large metropolitan area in the United States. The first sample was administered the CTS2 in its usual format. The second sample was administered a version of the CTS2 that presented items on one’s partners’ behavior first, followed by self-reported behavior. Results revealed that concordance rates among violent couples were higher in the group administered the CTS2 in its altered format, particularly agreement on male IPV perpetration. However, when agreement on minor and severe IPV was examined separately, concordance rates between groups were relatively similar for severe IPV. These findings suggest that altering the item presentation of the CTS2 may improve the interrater reliability of the Physical Assault Scale of the CTS2. Additional results are discussed.